2002
DOI: 10.1016/s0167-9457(02)00178-1
|View full text |Cite
|
Sign up to set email alerts
|

Intentional and attentional dynamics of speech–hand coordination

Abstract: Interest is rapidly growing in the hypothesis that natural language emerged from a more primitive set of linguistic acts based primarily on manual activity and hand gestures. Increasingly, researchers are investigating how hemispheric asymmetries are related to attentional and manual asymmetries (i.e., handedness). Both speech perception and production have origins in the dynamical generative movements of the vocal tract known as articulatory gestures. Thus, the notion of a ''gesture'' can be extended to both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
46
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 127 publications
6
46
0
1
Order By: Relevance
“…Finally, we wanted to understand the coupling relationship between each of the three tongue segments of interest and the jaw during liquid swallowing and to explore whether this coupling would become stronger [49,52] or weaker [39,53] at faster frequencies of reiterated swallowing (i.e., sequential swallowing). Coupling strength is typically reflected in the motor control literature using one of two characteristics: (1) frequency entrainment or (2) the variability of relative phase.…”
Section: Research Questionsmentioning
confidence: 99%
“…Finally, we wanted to understand the coupling relationship between each of the three tongue segments of interest and the jaw during liquid swallowing and to explore whether this coupling would become stronger [49,52] or weaker [39,53] at faster frequencies of reiterated swallowing (i.e., sequential swallowing). Coupling strength is typically reflected in the motor control literature using one of two characteristics: (1) frequency entrainment or (2) the variability of relative phase.…”
Section: Research Questionsmentioning
confidence: 99%
“…The findings showed that students in all disciplines became aware of the importance of threshold concepts, experienced the liminal space of oscillation between knowing and not knowing, and were passing through a portal of understanding at varying rates and by means of varied teaching strategies. The student learning experiences and achievement data support the idea that phase transitions and their anticipatory signatures (e.g., loss of stability) are common across a broad range of complex systems and disciplines, including human learning (Treffner & Peter, 2002).…”
Section: The Learning Experiencementioning
confidence: 57%
“…According to Meyer and Land (2003), after initially encountering a TC, students may spend time in a 'liminal' state'-which is akin to a phase transition observed in dynamical systems and cognitive development (Haken, Kelso, & Bunz, 1985;Stephen, Boncoddo, Magnuson, & Dixon, 2009;Treffner & Peter, 2002)-before crossing the threshold to deep understanding. Until students cross the threshold they are only able to mimic deep understanding and are therefore unable to solve new problems in diverse situations.…”
Section: Introductionmentioning
confidence: 99%
“…However, certain reference books about polyrhythmic structures treat them as the development of psycho-motor skills (e.g., Magadini, 2001;Yavuzoğlu, 2011). However, many studies of the correct performance of polyrhythmic structures claim that practicing these structures as cognitive processes is very effective (e.g., Bogacz, 2005;Jagacinski et al, 1988;Jagacinski et al, 2000;Riley, Amazeen, Amazeen, Treffner, & Turvey, 1997;Treffner and Peter, 2002).…”
Section: Discussionmentioning
confidence: 99%